Solving a bilevel strategic offering model for a generation company in a hydrothermal energy market: A new convexification approach - Lêdo, João A.S. [UNESP]; Nepomuceno, Leonardo [UNESP]; Conejo, Antonio J. (Elsevier, 2024)
This paper proposes a bilevel strategic offering (SO) model suitable for a strategic company (SC) that operates in a hydro-dominated day-ahead energy market. The upper-level model of the proposed SO model maximizes the SC's profits, while the lower-level model embodies a hydrothermal market clearing (MC). This MC incorporates detailed hydro and thermal constraints for units of both the SC and non-strategic companies (NSC), in addition to the network constraints. The proposed solution approach entails replacing the lower-level model with its corresponding primal and dual constraints, along with a strong duality equality constraint. This leads to a non-convex mathematical programming with equilibrium constraints (MPEC) model, which is then reformulated to feature only a single bilinear term in its structure. Finally, the recast MPEC model is convexified around an initial point and solved iteratively until a convergence criteria is achieved. The model and solution approach proposed are evaluated on an adapted version of the IEEE 24-bus system, exploring scenarios where the SC acts strategically or non-strategically (perfect competition).
Keywords: Bilevel optimization problems; Day-ahead energy market; Market power; Strategic offering; Bilevel; Day-ahead energy markets; Level model; Market clearing; Market Power; Mathematical programming with equilibrium constraints; Solution approach; Strategic companies